1992
DOI: 10.1016/0002-8703(92)90935-o
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing immediate results, complications, and short-term follow-up status after inoue balloon mitral valvotomy: A North American multicenter study

Abstract: Clinical trials with the moue mitral valvotomy balloon have recently begun in the United States. We assessed the effects of 17 demographic, echocardiographic, procedural, and hemodynamic variables on the immediate results, complications, and short-term follow-up of 200 patients in 15 centers undergoing valvotomy with this device. The study population had a mean age + SD of 53 t-15 years, and the total echocardiographic score was 7.2 k 2.4. Valvotomy was technically successful in 96.5% of procedures and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
44
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 26 publications
10
44
1
1
Order By: Relevance
“…[5][6][7][8][9][10]12,15 Including poor immediate results leads to overestimation of the predictive value of valve anatomy on late results because valve anatomy is a strong predictor of procedural success. 21,22,34 A recent series including only good immediate results of PMC did not identify valve anatomy as a significant predictive factor of late functional results in multivariable analysis. 14 The interaction between rhythm and NYHA class shows that a higher initial NYHA class is a predictive factor of poor late functional results only in patients in atrial fibrillation.…”
Section: Predictive Factors Of Poor Late Functional Resultsmentioning
confidence: 92%
“…[5][6][7][8][9][10]12,15 Including poor immediate results leads to overestimation of the predictive value of valve anatomy on late results because valve anatomy is a strong predictor of procedural success. 21,22,34 A recent series including only good immediate results of PMC did not identify valve anatomy as a significant predictive factor of late functional results in multivariable analysis. 14 The interaction between rhythm and NYHA class shows that a higher initial NYHA class is a predictive factor of poor late functional results only in patients in atrial fibrillation.…”
Section: Predictive Factors Of Poor Late Functional Resultsmentioning
confidence: 92%
“…Clinical studies have demonstrated its immediate, short-and long-term efficacy [6][7][8][9][10] . It has also been successfully performed in children [11][12][13][14][15][16][17][18][19] and during pregnancy [20][21][22] . Acute mitral regurgitation remains the main complication of mitral valvuloplasty and the stepwise balloon dilatation [23,24] has not been demonstrated to decrease this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Acute mitral regurgitation remains the main complication of mitral valvuloplasty and the stepwise balloon dilatation [23,24] has not been demonstrated to decrease this problem. Other complications, such as heart perforation, are rare [12] . Arterial complications are uncommon: vascular repair has been described in 0·1-1·0% of patients [25][26][27] , the need for blood transfusion in 0·01-0·5% [25,26,28] and the development of arteriovenous fistula in 0·01% of cases [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic insufficiency 1 Table 4 -Death causes during follow-up years [7][8][9][10][11][12][13][14][15][16][17][18] , however, the studied populations differ in their socioeconomic, ethnic, cultural and aging profiles, besides clinical and echocardiograph characteristics, from those found in our sample. All these particularities stick out the importance of knowing the long-term results of MVBC in the national context, which is represented by scarce but valuable studies 7,23 .…”
Section: Morbid Obesitymentioning
confidence: 99%
“…After the procedure, the immediate improvement of the valvar area and the survival without medium and long-term events [2][3][4] are comparable to the surgical commissurotomy 5,6 . Many factors have been suggested as determinants of late MVBC success, including: age, morphological aspects, cardiac rhythm, cardiac debt, mitral valve area (MVA) and experience of the intervention center [7][8][9][10][11][12][13][14][15][16][17][18] . However, there are still uncertainties with regard to these variables' predictive power, for the results are not homogeneous and some researchers did not found association of the abovementioned factors with long-term results 7,[9][10][11][12][13][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%